Progress of additive manufacturing in fabrication of foot orthoses for diabetic patients: A review - Komal Chhikara; Gurpreet Singh; Shubham Gupta; Arnab Chanda (Annals of 3D Printed Medicine, 2022)
The diabetic prevalent population is increasing day by day, which further increases the cases of diabetic ulceration, loss of sensation in the plantar region of the foot, and amputations in severe patients. These complications can be managed up to some extent by using modified shoes, offloading orthosis, etc. In recent advances, the use of additive manufacturing (i.e., 3D printing) to fabricate orthosis for diabetic patients is pioneering. The method of 3D printing of the foot orthosis for the diabetic foot management can be used along with the traditional methods. This review article will provide extensive literature on the pathophysiology of diabetes, the related complications and management techniques, and the use of additive manufacturing in the orthosis fabrication methods and its progress.